A patient-centered care for the management of children with rare diseases: collaboration between physicians, nurses, and patients - O.R. Boyarchuk; I.M. Antoniuk (Zaslavsky O.Yu., 2023)
The purpose of our study was to determine the effective strategies of patient-centered care for children with rare diseases and the role of healthcare professionals' collaboration with patients in implementing this approach. Patient-centered care, which revolves around respecting patients' values, preferences and needs, involving their families and friends, coordinating and integrating the care, promoting awareness, communication, and education, ensuring physical comfort, emotional support, and reducing fear and anxiety of patients, continuity and accessibility, has emerged as the most effective model of medical care for patients with rare diseases. To successfully implement this approach, it is crucial to have a targeted institutional policy with the active involvement of both institutional leaders and healthcare professionals in cooperation with patient organizations. This collaboration helps understand and address patients' needs, set specific goals and objectives, and enhance medical staff education and patient awareness, which are integral to the effectiveness of the approach. Family-oriented rounds as a form of patient-centered care contribute to increased patient satisfaction, improved communication between medical staff and patients/families, reduced stress levels associated with hospitalization, increased patient awareness and safety, and facilitate collaborative decision-making regarding diagnosis, treatment, and discharge planning. Coordination of care for patients with rare diseases is a fundamental aspect of integrated care across different levels. Through collaboration between the medical community and patient organizations, significant progress has been made in improving the diagnosis and treatment of rare disease patients, implementing evidence-based treatment standards, and incorporating best global practices. The cooperation with international professional and patient organizations since the first days of Russian aggression against Ukraine has been invaluable in saving the lives of patients with rare diseases and serious conditions.